Radical Changes in Political Campaign Strategy Prabowo Subianto's in the 2024 Presidential Election Indonesia: - - Erik Ardi yanto (Jurnal Komunikasi Ikatan Sarjana Komunikasi Indonesia, 2025)
The 2024 presidential election in Indonesia witnessed significant changes in the political campaign strategy of Prabowo Subianto, characterized by a radical departure from previous approaches. This research employs critical discourse analysis methods and documentation studies to analyze the transformative shifts in Prabowo's campaign tactics. The findings reveal a strategic rebranding of Prabowo's image, transitioning from a firm and temperamental figure to a more cheerful and humanistic persona. This rebranding was facilitated by the adoption of shallow political gimmicks, including "gemoy memes," "free lunch," and "dance okay gas," which were disseminated extensively on social media platforms. Additionally, the campaign strategically distorted historical records related to human rights violations and other contentious issues, effectively burying Prabowo's previous track record. Despite controversies surrounding the election, Prabowo's rebranded communication approach succeeded in capturing the support of novice voters, particularly from the younger generation. The research concludes that these radical changes in campaign strategy were instrumental in Prabowo's electoral success, as evidenced by preliminary voting data indicating significant support from Generation Z voters.